2013
DOI: 10.5194/amtd-6-10617-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Airborne emission measurements of SO<sub>2</sub>, NO<sub>x</sub> and particles from individual ships using sniffer technique

Abstract: Abstract. A dedicated system for airborne ship emission measurements of SO2, NOx and particles has been developed and used from several small aircrafts. The system has been adapted for fast response measurements at 1 Hz and the use of several of the instruments is unique. The uncertainty of the given data is about 20.3% for SO2 and 23.8% for NOx emission factors. Multiple measurements of 158 ships measured from the air on the Baltic and North Sea during 2011 and 2012 show emission factors of 18.8 ± 6.5 g kgfue… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This is in agreement with earlier onboard measurements 13,18 and also with plume measurements. 1921 The emission factor for PN when using the TD was 1.36 × 10 15 /kWh; thus the solid fraction represents about 16% of the PNs. This value is lower than the value reported by Jonsson et al 19 performing plume measurements within an SECA that limits the SFC to 1%.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with earlier onboard measurements 13,18 and also with plume measurements. 1921 The emission factor for PN when using the TD was 1.36 × 10 15 /kWh; thus the solid fraction represents about 16% of the PNs. This value is lower than the value reported by Jonsson et al 19 performing plume measurements within an SECA that limits the SFC to 1%.…”
Section: Discussionmentioning
confidence: 99%
“…Three measurement methods, including engine tests, onboard tests and plume tracking, are usually reported in the literature. However, most of the previous studies focused on the size-resolved particle number distributions (Wu et al, 2018;Cappa et al, 2014;Beecken et al, 2014;Moldanová et al, 2013;Juwono et al, 2013;Diesch et al, 2013;Alfoeldy et al, 2013;Winnes and Fridell, 2010;Kasper et al, 2007;Cooper, 2003), which reported that the total particle number concentrations were dominated by ultrafine particles (nucleation mode) or fine particles. For example, the mean particle diameter was between 25 and 40 nm for a two-stroke marine-diesel engine (Kasper et al, 2007) and between 40 and 60 nm for a fourstroke marine-diesel engine measured on a test bench (Petzold et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The fuel sulphur limit is still 3.5% outside SECA but is planned to be restricted to 0.5% in 2020. Studies of chemical composition of 30 ship PM have shown that the mass is typically dominated by organic matter, sulphate, and black carbon (Zetterdahl et al, 2016;Cappa et al, 2014;Lu et al, 2006;Anderson et al, 2015;Beecken et al, 2014). The relative distribution of these species depend partly on fuel sulphur content (Lack et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of CO2 can be used to estimate emission factors of gases and particles. NOx emissions from ships have also been shown to depend on, at least, both fuel type and on ship speed (Beecken et al, 2014;IPCC, 2013). https://doi.…”
Section: Introductionmentioning
confidence: 99%